A transversalidade da educação ambiental: parâmetros curriculares e concepções pedagógicas no curso de física da uern câmpus central, mossoró/rn - Paiva, Emanuella Rodrigues Veras da Costa (Universidade Federal Rural do Semi-Árido, 2019)
Through the Environmental Education National Policy (Política Nacional de Educação Ambiental – PNEA), environmental education should be developed in every educational level, as an integrated educational practice, continuous, permanent and in a crosssectional and interdisciplinary way. In tertiary education, the themes related to environmental education allow the promotion of aspects related to citizenship, sustainability and professional responsibility with environment preservation. However, in the literature, there is not a specific recipe to address environmental issues in graduation courses that meets what advocates PNEA and the Education Guidelines and Framework Law (LDB), what turns it into a challenge that requires pedagogical projects that cohere with this proposal and with teachers’ qualification. In this context, the aim of this study is to analyze the approach of Environmental Education in the graduation course of Physics at the central campus of the State University of Rio Grande do Norte (UERN) in Mossoró (Brazil). Qualitative and quantitative techniques were adopted on the methodological proceedings. An investigation on the following institutional documents was carried out: Institutional Development Plan (Plano de Desenvolvimento Institucional – PDI), Institutional Pedagogical Project (Projeto Pedagógico Institucional – PPI), Course Pedagogical Project (Projeto Pedagógico do Curso – PPC) and other important documents related to the pedagogical proceedings of the scope of the course. When considering the legal side, the PNEA and the National Curricular Guidelines (DCNs) to the course of Physics, among other regulations, were analyzed. It was also carried out a detailed mapping of the data that refer to the projects and activities of research and extension projects, in order to verify if there are crosssectional themes related to environment issues on these actions. The quantitative analysis was constituted by the application and analysis of a structured questionnaire with closed ended questions in Likert scale and open questions, performed with 100% of the professors of the course. The environmental education thematic is present on UERN’s and Physics’ course formal documents, and they are coherent with the legislation. On the actions of teaching, research and extension, systematic actions of the permanent cross-sectional approach were not found. The teaching staff understands the necessity of performing the pedagogical proposal related to the environmental education, however, their pedagogical practices are strongly focused on their stricto sensu education. The understanding that the pedagogical proposal is important on the part of the professors, what was observed on this study, may be the way to lead classroom praxis to reflect directly on the academic education of the Physics course’s students of UERN. The continuous education of the professors, the assistance, evaluation and meta-evaluation of the teaching, research and extension activities are important strategies on the effectiveness of environment education as a permanent cross-sectional theme
Keywords: tema transversal; aspectos pedagógicos; educação e sustentabilidade; cross-sectional theme; pedagogical aspects; education and sustainability; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES